Academic Developmental-Behavioral Pediatric Faculty at Developmental-Behavioral Pediatric Research Network Sites: Changing Composition and Interests. Issue 9 (November 2017) - Roizen, Nancy; Stein, Ruth E. K.; Silver, Ellen J.; High, Pamela; Augustyn, Marilyn C.; Blum, Nathan J.
ABSTRACT: Objective: To obtain and review workforce data, given the critical demand for developmental pediatricians (DPs). Methods: Survey of demographics and professional activities of DP physician faculty at Developmental-Behavioral Pediatric (DBP) Research Network fellowship training sites. Results: Of the eligible providers at 12 centers, 76% (n = 50) completed surveys. They were on average 50 years old and mostly female (86%), white (82%), and working full time (74%). Full timers reported a mean 50.2-hour week made up of clinical work (23.2 hours), supervision (5.9 hours), research (8.8 hours), administration (5.2 hours), teaching (1.5 hours), advocacy (1.1 hours), and other (4.3 hours). Compared with those >10 years out of training, the 20 physicians (40%) ⩽10 years out of fellowship were more likely to be nonwhite ( p = .003). Overall faculty interest/expertise (I/E) was highest in autism (90%) and attention deficit hyperactivity disorder (ADHD; 86%). Those ⩽10 years out of fellowship had more I/E in autism ( p = .05) and less in chronic illness ( p = .06) and parenting ( p = .06). DPs practiced most frequently in a General DBP Clinic (74%), followed by clinics specific for: Autism (36%), Toddlers (22%), ADHD (20%), Infants (18%) and Preschoolers (16%). Common clinics were Autism (9), syndrome specific (9), ADHD (6), and School-Aged (5). Conclusion: Developmental pediatrician faculty in DBP training sites feed the pipeline of much needed DP physicians. This survey provides baseline information on the professional activities of DP faculty and found changing demographics and I/E as well as a wide variety of clinic types.